Impact of Long-Term Loading on Reinforced Concrete Beams Made with Partial Replacement of Coarse Aggregates with Recycled Aggregates from Old Concrete - Oad, M.; Buller, A. H.; Memon, B. A.; Memon, N. A. (Engineering, Technology & Applied Science Research, 2019)
This research work presents an experimental evaluation of the effect of sustained loading on reinforced concrete beams made with 50% replacement of natural coarse aggregates with aggregates from old concrete. A total of 9 RC beams were cast, 6 with natural coarse aggregates and 3 with recycled concrete aggregates. All beams were cured for 28 days in standard fashion. Among the first batch, 3 beams were used to test under short term loading till failure. An application of 50% of short-term loading followed on all beams assembled on purpose made frames. All beams were monitored for deflection, strain, and cracking. Both deflection and strain remained within limits. Crack monitoring revealed maximum crack width 0.5 mm. After six months of sustained load, beams were removed from the frames and tested in universal load testing machine with central point load till failure. The load-deflection pattern of all beams was observed to be almost similar and 22.12% higher in recycled concrete beams than all-natural aggregate beams. The results show promising use of recycled concrete aggregates in new concrete subjected to sustained loading.